2021
DOI: 10.1093/cid/ciab109
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Risk Prediction Model for Carbapenem-resistantEnterobacteriaceaeInfection After Liver Transplantation: A Multinational Cohort Study

Abstract: Background Patients colonized with carbapenem resistant Enterobacteriaceae (CRE) are at higher risk of developing CRE infection after liver transplantation (LT) with associated high morbidity and mortality. Prediction model for CRE infection after LT among carriers could be useful to target preventive strategies. Methods Multinational multicenter cohort study of consecutive adult patients underwent LT and colonized with CRE b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 26 publications
2
41
1
Order By: Relevance
“…The high risk of invasive infections in recipients colonized by MRSA [ 47 , 48 ] or KPC [ 7 , 8 ] commonly increases morbidity and mortality. In patients with CRE, BSI conferred a significantly lower survival rate [ 7 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high risk of invasive infections in recipients colonized by MRSA [ 47 , 48 ] or KPC [ 7 , 8 ] commonly increases morbidity and mortality. In patients with CRE, BSI conferred a significantly lower survival rate [ 7 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplantation is a lifesaving treatment for acute and chronic end-stage liver diseases. Infections in transplant recipients account for the main cause of mortality and morbidity with rates of up to 80% [ 6 , 7 , 8 ] despite advanced surgical techniques, new immunosuppressive drugs, prophylactic antibiotics, vaccination, and infection control strategies. The increasing incidence of MDR infections has raised clinical needs in terms of infection control strategies and empiric and targeted antibiotic and antiviral therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver transplantation (LT) community is already familiar with this concept. Recently, Kim et al showed that “MELD 3.0 correctly reclassified a net of 8.8% of decedents to a higher MELD tier, affording them a meaningfully higher chance of transplantation, particularly in women.” ( 8 ) Furthermore, the decision curve analysis helped a multinational cohort study of consecutive adult LT patients to detect cabapenem‐resistant Enterobacteriacae infection after LT. ( 9 ) Although these tools may be a priori complicated, authors publishing in Liver Transplantation should be encouraged to follow them for a comprehensive score evaluation.…”
Section: Of Nacseld Easl‐clifmentioning
confidence: 99%
“…detect cabapenem-resistant Enterobacteriacae infection after LT. (9) Although these tools may be a priori complicated, authors publishing in Liver Transplantation should be encouraged to follow them for a comprehensive score evaluation.…”
mentioning
confidence: 99%